Conceptual Model of Knowledge Management and Social Media to Support Learning Process in Higher Education Institution - Tanty Oktavia; Harco Leslie Hendric Spits Warnars; Suroto Adi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Nowadays social media has tremendously transformed organizational business process of institution. Higher Education as a place with the majority generation Y, that advances to use technology should realize these situations. With this social media platform, institution may facilitate the knowledge transfer process, then to support collaborative learning from e-learning to social learning. Referring to this phenomenon, this research will design the integration of concepts of knowledge management and social media as a framework to identify the significant components and its relationship to support each other. In this research, we use a systematic literature review from journal and text book to construct this collaboration model. The outcome of this study is collaboration model of knowledge management and social media to support learning process in higher education institution.